Innovative Education: Facilitation - Effective Method of Organizing the Educational Process - Annakulova Saltanat Karshiboyevna; Israilov Khabibulla Abdurazokovich (Genius Journals, 2023)
Facilitation (facilitation) in English. "relief", facilis means "to ease" or facilitate). In the management of the facilitator, the participants can solve problems and increase the efficiency of their activities due to their observation and communication with their partners in the team. vocabulary.ru.
Keywords: Facilitation; relief; Consensus is an agreement; Delphi method (prediction)